2016
DOI: 10.1002/aur.1682
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modifications associated with ketogenic diet treatment in the BTBRT+Tf/J mouse model of autism spectrum disorder

Abstract: Although our study supports many of the previously known impairments associated with ASD, such as excessive myelin formation and impaired GABAergic transmission, the RNAseq data and pathway analysis utilized here identified new therapeutic targets for analysis, such as Vitamin D pathways and cAMP signaling. Autism Res 2017, 10: 456-471. © 2016 International Society for Autism Research, Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…The mice were born and reared in a quiet, temperature-controlled room and entrained to a 12-hour light-dark cycle. After weaning at postnatal day 21 (PD21), the mice were placed on either standard diet (SD) or ketogenic diet (KD; 6.3:1 ratio by weight of fat to carbohydrate plus protein; Bio-Serv F3666, Frenchtown, NJ, USA) for 10-14 days [73,74] based on our previous experiments [38,45]. F3666 is a ketogenic chow composed of lard, butter, corn oil, casein, cellulose, mineral mix, vitamin mix, and dextrose.…”
Section: Animals and Dietary Proceduresmentioning
confidence: 99%
“…The mice were born and reared in a quiet, temperature-controlled room and entrained to a 12-hour light-dark cycle. After weaning at postnatal day 21 (PD21), the mice were placed on either standard diet (SD) or ketogenic diet (KD; 6.3:1 ratio by weight of fat to carbohydrate plus protein; Bio-Serv F3666, Frenchtown, NJ, USA) for 10-14 days [73,74] based on our previous experiments [38,45]. F3666 is a ketogenic chow composed of lard, butter, corn oil, casein, cellulose, mineral mix, vitamin mix, and dextrose.…”
Section: Animals and Dietary Proceduresmentioning
confidence: 99%
“…To examine the underlying mechanism of the abnormal cerebellar development and connection formation in BTBR mice, we performed RNA-Seq in whole cerebella tissue of WT and BTBR mice at postnatal day 14. Previous studies were performed in other brain regions of BTBR mice vs WT mice (35)(36)(37), but few studies were done in cerebella. We identified 3992 differentially expressed genes (P<0.05), with 1858 upregulated and 2134 downregulated (Fig.6 A) (Fig.s4), the critical genes were identified, and significantly increased TRPC6 was a highly suspicious candidate in BTBR mice (Fig.6 C).…”
Section: Dysregulated Trpc Genes Impaired Cerebellar Development In Bmentioning
confidence: 99%
“…BTBR mice display deficits in social interaction and communication assays and exhibit repetitive and stereotyped behaviors. During the relatively short time since its discovery as an ASD model, the BTBR strain has been increasingly used to study the etiology and to uncover potential interventions for ASD (Moy et al, 2007 ; McFarlane et al, 2008 ; Llaneza et al, 2010 ; Ruskin et al, 2013 ; Cheng et al, 2016 ; Mychasiuk and Rho, 2016 ; Newell et al, 2016 ). Ruskin and colleagues reported that the BTBR mice showed decreased sociability in the three-chamber test, decreased self-directed repetitive behavior, and improved social communication in a food preference assay after being fed a KD (Ruskin et al, 2013 ).…”
Section: Metabolic Therapy and Asd—evidence From Animal Modelsmentioning
confidence: 99%